Impact of Different Pasteurization Techniques and Subsequent Ultrasonication on the In Vitro Bioaccessibility of Carotenoids in Valencia Orange (Citrus sinensis (L.) Osbeck) Juice - Lara Etzbach; Ruth Stolle; Kerstin Anheuser; Volker Herdegen; Andreas Schieber; Fabian Weber (Antioxidants, 2020)
The effects of traditional pasteurization (low pasteurization, conventional pasteurization, hot filling) and alternative pasteurization (pulsed electric fields, high pressure processing), followed by ultrasonication on the carotenoid content, carotenoid profile, and on the in vitro carotenoid bioaccessibility of orange juice were investigated. There was no significant difference in the total carotenoid content between the untreated juice (879.74 µg/100 g juice) and all pasteurized juices. Significantly lower contents of violaxanthin esters were found in the high thermally-treated juices (conventional pasteurization, hot filling) compared to the untreated juice, owing to heat-induced epoxy-furanoid rearrangement. The additional ultrasonication had almost no effects on the carotenoid content and profile of the orange juices. However, the in vitro solubilization and the micellarization efficiency were strongly increased by ultrasound, the latter by approximately 85.3–159.5%. Therefore, among the applied processing techniques, ultrasonication might be a promising technology to enhance the in vitro bioaccessibility of carotenoids and, thus, the nutritional value of orange juice.